Effect of two new antisecretory drugs on fluid and electrolyte transport in a patient with secretory diarrhoea. Issue 5 (May 1986) - Edwards, C; Cann, P A; Read, N W; Holdsworth, C D
Abstract : The effect of oral lidamidine hydrochloride and subcutaneous long acting somatostatin analogue, SMS 201-995, on stool output and salt and water transport in the small intestine was investigated in a patient with gross secretory diarrhoea caused by a vasoactive intestinal polypeptide (VIP) secreting tumour in the liver. Transport in the jejunum and ileum were assessed by steady state perfusion techniques. Under basal conditions, the patient was absorbing fluid and electrolytes from the jejunum and ileum, but at rates that were abnormally low. Lidamidine had no effect on either intestinal transport or stool frequency and output. SMS 201-995 increased intestinal absorption in the jejunum and ileum, reduced plasma VIP concentrations, daily stool frequency and weight, and enabled the patient to resume a normal diet without oral or intravenous fluid and electrolyte supplements. After two months of treatment, medical control was becoming increasingly difficult and stool output had risen again to 2 litres per day. Surgical resection, fortunately, was possible and led to resolution of symptoms and normal plasma VIP concentrations.